Cultural socialization and its relation to the attitude of religious tolerance among Muslim and Buddhist students in Prince of Songkhla University - Mutsalem Khareng,; Jaffary Awang, (Universiti Kebangsaan Malaysia, 2012)
Interaction and communication between religions often develop a harmony culture. Without a good interaction and communication, it can emerge prejudice. It means that interaction in the context of a different culture and religion plays an important role in shaping the integration value. In the context of students at Prince of Songkhla University consisting of Muslims and Buddhists who often interact among each other. The question is how far the conflict in Southern Thai has influenced the communication patterns? Hence, this article discusses the patterns of interaction and communication between Muslims and Buddhists at universities. In addition, how far the interaction and communication among both side have created a religious tolerance. The methodology used in the study is qualitative and quantitative approach using questionnaires and interviews. This study shows that most students have a good interaction and communication. In addition, this study also shows that there are a relationship between interaction and communication with the a ttitude of religious tolerance at a strong level